EVALUATION OF EDUCATION AND TRAINING SOCCER REFEREE IN WEST JAVA PSSI - SYAMSUDAR, BANGBANG (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The purpose of this study was to evaluate educational programs and training referees in the Association of West Java PSSI .: (1) The policy goal umpire education and training programs, (2) Resources educational programs and training referees in PSSI Association of West Java province, (3) education programs and training referees, (4) Product educational programs and training referees. This study uses a model of CIPP Stufflebeam. The technique of collecting data through observation, interviews and documentation study, researchers naturally interact with research subjects. The results showed that: (1) The purpose of education programs and training referees C-2 at the Association of the Province of West Java PSSI, has no legal basis and purpose that can be accounted for in order to increase the competence of the referee. Implementation of the program is in line with the development goals of HR refereeing quality and maintain regeneration referee who has the character and responsibilities are qualified, (2) resource planning program delivery pendidikdan and training referees C-2 at the Association of Provincial PSSI West Java, has been done with regard design training, curriculum, SAP, competent instructor, use of media, the use of the method, the formation of a committee, availability of accommodation, and facilities and infrastructure., 3) the implementation process of the implementation of educational programs and training referees C-2 at the Association of Provincial PSSI West Java, run in accordance with the curriculum and training program objectives. (4) There is a change in the participants knowledge of training in the form of increase in value of knowledge of the rules of the game (FIFA).